Conservative Management of Medication-Related Osteonecrosis of the Jaws (MRONJ): A Retrospective Cohort Study - Elena M. Varoni; Niccolò Lombardi; Giulio Villa; Alberto Pispero; Andrea Sardella; Giovanni Lodi (MDPI AG, 2021)
Background: Medication-related osteonecrosis of the jaw (MRONJ) is a severe side effect of bisphosphonates and anti-resorptive drugs prescribed for treatment of severe osteoporosis, Paget's disease, and bone malignancies. The aim of this study was to evaluate the clinical outcome of a combined pharmacological and surgical management strategy on patients affected by MRONJ. Materials and methods: Medical records of patients with MRONJ were retrospectively examined to collect clinical history data. Conservative management included an initial pharmacological phase with antibiotics and antiseptic agents, followed by surgical intervention to remove bone sequestrum. Primary outcomes were healing from MRONJ at short term (1 month after surgery) and at longer term (3 months after surgery). Secondary outcome was assessment of recurrences at longer-term follow-up. Results: Thirty-five patients were included in the study with mean follow-up of 23.86 ± 18.14 months. Seven cases showed spontaneous exfoliation of necrotic bone during pharmacological therapy, which in one case did not require any further intervention. At 1-month posttreatment, 31 out of 35 (88.5%) patients showed complete healing. The 25 patients who were followed for at least 3 months revealed a healing rate of 92% (23/25). Recurrences occurred in 7 patients out 23 who showed the long-term healing, after a mean period of 7.29 ± 3.45 months. The prognostic score (University of Connecticut Osteonecrosis Numerical Scale-UCONNS) was significantly higher (p = 0.01) in patients with poor healing as compared to complete healing, both at 1 and 3 months posttreatment. Conclusions: A MRONJ treatment approach based on a combined pharmacological and surgical treatment strategy showed a high rate of healing and few recurrences.